2017
DOI: 10.1371/journal.pone.0178126
|View full text |Cite
|
Sign up to set email alerts
|

Robot education peers in a situated primary school study: Personalisation promotes child learning

Abstract: The benefit of social robots to support child learning in an educational context over an extended period of time is evaluated. Specifically, the effect of personalisation and adaptation of robot social behaviour is assessed. Two autonomous robots were embedded within two matched classrooms of a primary school for a continuous two week period without experimenter supervision to act as learning companions for the children for familiar and novel subjects. Results suggest that while children in both personalised a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 74 publications
(79 reference statements)
1
114
0
1
Order By: Relevance
“…Personalization of the robot was defined in terms of nonverbal behaviour, linguistic content, and performance alignment. Specifically, the results from this study showed that children exhibited significantly increased learning only in the novel learning task in the personalized condition [Baxter et al 2017]. Although these three scenarios present themselves as extremely rich and challenging for social learning, especially because a robot was deployed in school for long-term educational gains, they were built for one-robot-one-student interactions.…”
Section: Robots In Educationmentioning
confidence: 86%
“…Personalization of the robot was defined in terms of nonverbal behaviour, linguistic content, and performance alignment. Specifically, the results from this study showed that children exhibited significantly increased learning only in the novel learning task in the personalized condition [Baxter et al 2017]. Although these three scenarios present themselves as extremely rich and challenging for social learning, especially because a robot was deployed in school for long-term educational gains, they were built for one-robot-one-student interactions.…”
Section: Robots In Educationmentioning
confidence: 86%
“…Additionally, children have shown to perceive robots that mimic empathy as their friends, even when explicitly instructed that the robot was behaving as their tutor, which indicates that interactions with robots capable of mimic human capabilities may lead to positive changes in the perception of a robot's role (Alves‐Oliveira, Sequeira, & Paiva, ). Other studies have shown that a robot delivering personalized tutoring behaviors can have a positive influence on children's learning (Baxter, Ashurst, Read, Kennedy, & Belpaeme, ) leading to an increase in positive emotions in children (Gordon et al, ). Moreover, in some studies children showed increased learning gains when a child acted as the robot's teacher.…”
Section: Positive Effects Of Humanization For Hrimentioning
confidence: 99%
“…We believe it is beneficial to frame the robot as a peer [5,7,24], because children are attracted to various attributes of a robot [33] and tend to treat a robot as a peer in long-term interactions [64]. Moreover, framing the robot as a peer could make it more acceptable when the flow of the interaction is suboptimal due to technical limitations of the robot (e.g., the robot being slow to respond or having difficulty interpreting children's behaviours).…”
Section: Framing the Robotmentioning
confidence: 99%
“…The tutor has to structure the interaction, needs to choose the skills to be trained, must adjust the difficulty of the learning tasks appropriately, and has to adapt its verbal and non-verbal behaviour to the situation. The importance of personalised adjustments in the robot's behaviour has been evidenced in research showing that participants who received personalised lessons from a robot outperformed others who received non-personalised training [5,45]. Suboptimal robot behaviour (e.g., too much, too distracting, mismatching, or in other ways inappropriate) can even hamper learning [35].…”
Section: Objectivementioning
confidence: 99%